Structural basis of hypoxic gene regulation by the Rv0081 transcription factor of Mycobacterium tuberculosis. Issue 9 (26th April 2019) - Kumar, Ashwani; Phulera, Swastik; Rizvi, Arshad; Sonawane, Parshuram J.; Panwar, Hemendra S.; Banerjee, Sharmistha; Sahu, Arvind; Mande, Shekhar C.
Abstract : The transcription factor Rv0081 of Mycobacterium tuberculosis controls hypoxic gene expression and acts as a regulatory hub in the latent phase of tuberculosis (TB) infection. We report here the crystal structure of Rv0081 at 2.9 Å resolution revealing that it belongs to the well‐known ArsR/SmtB family proteins. However, unlike other members in this family, Rv0081 has neither a metal‐binding domain nor does it possess Cys residues, suggesting an alternate mechanism of gene regulation. Our structural and biochemical analyses suggest the molecular basis for the recognition of self‐regulatory DNA sequences and a plausible mechanism of regulation of Rv0081 in the latent phase of TB infection. Database: Structural data are available in the Protein Data Bank under the accession number –6JMI Abstract :